Anthropometric characteristics of Chilean workers for ergonomic and design purposes. Issue 3 (4th March 2019) - Castellucci, H. I.; Viviani, C. A.; Molenbroek, J. F. M.; Arezes, P. M.; Martínez, M.; Aparici, V.; Bragança, S.
Abstract: Obtaining an appropriate match between a product and its end-users requires anthropometric data, which are typically outdated and show variations among different countries. Chile had its anthropometric data taken nearly 20 years ago, thus they are probably outdated. The purpose of this article is to describe some anthropometric characteristics of Chilean workers. An anthropometric survey involving 27 measures and five calculated body dimensions was conducted in 2016. The measurements were based on ISO 7250 and ISO 15535 to ensure the highest standards possible, and a total of 2946 workers, aged from 18 to 76 years old, participated in the survey. The results showed that Chilean workers have smaller dimensions than Dutch and US workers but have larger dimensions than South Koreans. The data presented in this article constitute the most up-to-date anthropometric dataset describing the dimensions of Chilean workers. Practitioner Summary: In Chile, women are smaller and weigh less than men, and both of these populations have high body mass index (BMIs). In addition, the Chilean population exhibits substantial differences compared with other international adult populations. The data presented in this article should be used as a reference when designing for Chilean workers.